ANALISIS PROFITABILITAS PERBANKAN SYARIAH DENGAN NET INTEREST MARGIN SEBAGAI VARIABEL MEDIASI - Agus Santhuso; Heny Herawati; Aam Karimah (Program Studi Perbankan Syari'ah Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2023)
Most people depend on financial services in their daily lives,therefore the survival of the banking industry is very important. The purpose of this study was analisis Profitability the effect of Fund Gap, Liquidity, and Efficiency Level with Net Interest Margin as a mediating variable for Bank Muamalat Indonesia for the 2014-2022 Period. This study uses a type of quantitative research using path analysis as data analysis. This study uses secondary data taken from quarterly financial reports I, II, III, IV which include Return On Asset (ROA), Net Interest Margin (NIM), Fund Gap (GAP), Loan To Deposit Ratio (LDR) / Financing To Deposit Ratio (FDR), and Operating Expenses Operating Income (BOPO) for the period 2014 to 2022. The data that has been obtained is then analyzed using the Eviews version 10 tool. The results showed that GAP has an insignificant positive on Net Interest Margin (NIM) but a significant negative on Return On Asset (ROA). While Liquidity (LDR) has a significant positive on Net Interest Margin (NIM) but has an insignificant positive on Return On Asset (ROA) and Efficiency Level (BOPO) has a significant negative on Net Interest Margin (NIM) but has an insignificant positive on Return On Asset (ROA). For Net Interest Margin (NIM) has a significant positive on Return On Asset (ROA). The results of path analysis show that Net Interest Margin (NIM) cannot mediate of Fund Gap on Profitability and Efficiency Level, but Net Interest Margin (NIM) can mediate of Liquidity on Profitability.